Globalization or Recolonization: The Muslim World in the 21st Century by Ali Mohammadi and Muhammad Ahsan (London: Ta-Ha Publishers Ltd, 2002. 196 pages.) (American Journal of Islam and Society, 2003)
Globalization has been a burning topic of interest for social scientists andthe general public for the last 2 decades. However, a Muslim discourse onglobalization has not been sufficiently developed. The current book seeksnot only to present a dramatic picture of the ummah within the globalizednetwork of mainly economic relations, but also offers policy solutions toget out of this crisis and create the Islamic ummah as an active actor inglobal economic and political affairs.As the title suggests, in this book globalization does not have the pos itiveconnotations that it has in liberal western scholarship. In fact, it is seenmore as a recolonization of the Third World, and, in particular, of theIslamic world. The first chapter lays the theoretical ground, the last oneconcludes the argument and gives a strategic plan to counter recolonization,while the other six chapters concentrate on different aspects of globaliza tion.What comes out of the comparative analyses between the developedand the developing non-Muslim and Muslim worlds is the striking fact thatMuslims score the lowest in almost all areas. Besides calling the Muslims'attention to this disconcerting plethora of problems, the authors masterfullydocument how the myth of interdependence fades away, notwithstandingevidence of the unequal treatment by the "global" economic and political institutions, when the Muslims' interests are at stake. In many instances, the economic and political variables go hand-in-hand with the informative ones that perpetuate and legitimize these unfair actions through a fundamentalist image of Muslims ...